A new rodent behavioral paradigm for studying closed-loop cursor control - Ayyaz, Ahsan (İstanbul Medipol Üniversitesi, Fen Bilimleri Enstitüsü, 2022)
Control of cursor on a PC monitor using a joystick is a standard paradigm to study the neural mechanisms involved in motor skill learning in human and non-human primates. This paradigm is also commonly used in non-human primates for the association of cursor movements with reward before initiation of brain-machine interface control tasks. However, this task, even in a simpler form, has not been available for rodents yet. In this work, we present a novel behavioral paradigm that enables rats to direct a cursor on a PC monitor by operating levers for reaching stationary targets. The control of the cursor is performed in a one-dimensional space depending on the limited cognitive and visual capabilities of rats. The behavioral setup mainly consists of a cage with transparent, plexiglass walls and a PC monitor outside the cage that is used to demonstrate a cursor and two opposite targets to be achieved using the cursor. The attention of the rats was shifted from inside the cage to the cursor and targets through shaping procedures presented here. In the cursor control paradigm, pressing one of two levers is used to move the cursor towards the randomly selected target and a lever release and press sequence was required for correcting the movements of the cursor when it does not move towards the selected target even though the correct lever is pressed. Three out of four rats were able to perceive cursor motion and its proximity from the trial-specific target and achieved inclusion criteria (i.e., 75% accuracy in 40 consecutive trials) for the final step after 52± 12 days of training, with a training session duration of 2.5 to 3 hours per day. The rats were able to detect the error in the trajectory of a cursor based on the visual feedback provided and the results showed that the rats have the visuomotor ability to correct the error in the trajectory. We have demonstrated a proof of concept for this paradigm, future studies will focus on the learning curve of mice for this paradigm. The paradigm presented here can be used to investigate the information processing principles in the neural circuits involved in cursor control based on visual feedback. The neuroscientific knowledge acquired through such studies can be used in the development of novel brain-machine interface decoders which operate by monitoring the neural information distributed across different motor-related structures in the brain. The present study also introduces the methods we developed for the fabrication of a new generation, ultra-flexible microelectrode arrays that can be used for dopamine measurement and electrophysiological recordings.

Bir kumanda kolu kullanarak PC ekranındaki bir imlecin kontrolü, insan ve insan olmayan primatlarda motor beceri öğreniminde yer alan nöral mekanizmaları incelemek için standart bir paradigmadır. Bu paradigma, beyin-makine arayüzü kontrol araştırmalarının başlamasından once, imleç hareketlerinin ödülle ilişkilendirilmesi için insan olmayan primatlarda yaygın olarak kullanılmıştır. Ancak, bu görev, daha basit bir biçimde bile, henüz kemirgenler için mevcut değildir. Bu çalışmada, sıçanların sabit hedeflere ulaşmak için levyeleri kullanarak PC monitöründeki bir imleci yönlendirmesini sağlayan yeni bir davranış paradigması sunmaktayız. İmlecin kontrolü, sıçanların sınırlı bilişsel ve görsel yeteneklerine bağlı olarak tek boyutlu bir alanda gerçekleştirilmektedir. Davranışsal deney düzeneği esas olarak şeffaf, pleksiglas duvarlı bir kafes ve bir kafesin dışında yer alan bir PC monitörü ve bu monitordeki imleç ve iki zıt hedeften oluşmaktadır. Sıçanların dikkati, burada sunulan eğitim prosedürleri aracılığıyla kafesin içinden imleç ve hedeflere kaydırılmaktadır. İmleç kontrol paradigmasında, imleci rastgele seçilen hedefe doğru hareket ettirmek için iki koldan birine bastırmak gereklidir ve imleç, seçilen hedefe doğru hareket etmediği durumlarda hareketlerini düzeltmek için levyeyi bırakma ve bastırma hareketi gereklidir. Deneylerimizde dört sıçandan üçü, imleç hareketini ve imlecin hedefe yakınlığını algılayabilmiş ve günde 2,5 ila 3 saat süren 52±12 günlük eğitimden sonra başarı kriterlerine (ardışık 40 denemede %75 doğruluk oranı) ulaşabilmiştir. Fareler, sağlanan görsel geri bildirime dayalı olarak bir imlecin yörüngesindeki hatayı tespit edebildi ve sonuçlar farelerin yörünge hatasını düzeltmek için görsel motor yeteneğine sahip olduğunu gösterdi. Bu paradigma için bir kavram kanıtı gösterdik, gelecekteki çalışmalar bu paradigma için farelerin öğrenme eğrisine odaklanacaktır. Bu çalışmada sunulan paradigma, görsel geribildirime dayalı imleç kontrolünde yer alan sinir devrelerindeki bilgi işleme ilkelerini araştırmak için kullanılabilir. Bu paradigmayı kullanarak gerçekleştirilen çalışmalar yoluyla elde edilen sinirbilimsel bilgi, beyindeki farklı motor kontrolle ilgili yapılar arasında dağılmış haldeki sinirsel bilgileri izleyerek çalışan yeni beyin-makine arayüzü şifre çözücülerinin geliştirilmesinde kullanılabilecektir. Çalışmada ayrıca yeni nesil yüksek yumuşaklığa sahip dopamin ölçümü ve elektrofizyolojik kayıtlarda kullanılabilecek mikroelektrot dizilerinin üretim yöntemleri tanıtılmaktadır.
Kapalı-devre imleç kontrolünün araştırılması için yeni bir sıçan davranış paradigması
Keywords: Behavior; Motor Skill Learning; Visual Feedback; Trajectory Control; Ultraflexible Microelectrode; Davranış; Motor Yetenek Öğrenme; Görsel Geribildirim; Gidiş Yolu Kontrolü; Yüksek Yumuşaklıkta Mikroelektrot